2018
DOI: 10.1038/s41598-018-22994-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green tea on miRNA and microbiome of oral epithelium

Abstract: Consumption of green tea (GT) extracts or purified catechins has shown the ability to prevent oral and other cancers and inhibit cancer progression in rodent models, but the evidence for this in humans is mixed. Working with humans, we sought to understand the source of variable responses to GT by examining its effects on oral epithelium. Lingual epithelial RNA and lingual and gingival microbiota were measured before and after 4 weeks of exposure in tobacco smokers, whom are at high risk of oral cancer. GT con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 98 publications
(97 reference statements)
0
18
0
Order By: Relevance
“…All these food-derived miRNAs can presumably interact with oral and gut microbiota (167,168). On this basis, exogenous miRNAs may act as bacterial small RNA to interfere with bacterial gene expression modulating the entire microbiome (169,170).…”
Section: Possible Mechanisms Of Carcinogenesis Induced By Dysbiosismentioning
confidence: 99%
“…All these food-derived miRNAs can presumably interact with oral and gut microbiota (167,168). On this basis, exogenous miRNAs may act as bacterial small RNA to interfere with bacterial gene expression modulating the entire microbiome (169,170).…”
Section: Possible Mechanisms Of Carcinogenesis Induced By Dysbiosismentioning
confidence: 99%
“…Several clinical trials also demonstrated the anticancer effect of tea and its components [110][111][112]. It was reported that green tea consumption (5 × 1 cup/day, four weeks) changed oral bacteria, which might be related to oral carcinogenesis [110].…”
Section: Anticancer Effect In Humansmentioning
confidence: 99%
“…Several clinical trials also demonstrated the anticancer effect of tea and its components [110][111][112]. It was reported that green tea consumption (5 × 1 cup/day, four weeks) changed oral bacteria, which might be related to oral carcinogenesis [110]. In another clinical trial involving 70 Algerian prostate cancer patients and 120 age-matched healthy subjects, daily consumption of 5 cups of infusion prepared from 2 g green tea for 6 months significantly decreased oxidative stress and prevented prostate cancer initiation [111].…”
Section: Anticancer Effect In Humansmentioning
confidence: 99%
“…After 4 weeks of GT drinking, human tissue exposed to probably the highest concentration of undiluted tea in the body, the tongue epithelium, showed on average no changes in gene expression due to inter-subject variability in levels of miRNA. Only after differential co-expression analysis, which can correct for a lack of a response in some subjects, did GT-induced changes in miRNA expression become evident [ 48 , 49 , 50 , 51 ]. Non-supervised hierarchical clustering of oral epithelial sample miRNA revealed a group of 5 out of 14 subjects who, after consuming GT, differed most from control subjects who did not consume GT [ 48 ].…”
Section: Significance Of Studying Gt Effects In Vivomentioning
confidence: 99%